FOREIGN EXPERIENCE IN IMPROVING THE EFFICIENCY OF THE SYSTEM OF STATE REGULATION OF INNOVATION ACTIVITIES - Zhurynov, G.M.; Isataeva, G.B.; Satybekova, E.G.; Orazova, B.B.; Abylkasym, A.B. (Scientific Journal of Pedagogy and Economics, 2020)
Therefore, the transition to an innovative economy requires the development of a network of regional innovation systems. At the same time, the regional innovation policy should be aimed at the formation of regional innovation clusters as the basis of the innovation system of the region, where the best conditions for the innovation process are located. Of particular interest are regions with high scientific potential (as a rule, they include scientific fences and a number of academic towns and other territories with high scientific potential), as they have a significant stock of developments ready for commercialization. It is on the basis of such territories that it is necessary to develop regional innovation clusters. Despite the fact that the problem has been studied and the high level of attention, many of its aspects remain unresolved. Many authors have pointed out the limited possibilities of using classical methods of evaluating investment projects for innovation, and thus the proposed alternatives have not been widely used. The practical and actual significance of the problems of management and evaluation of innovative projects and the use of the most effective methods for this purpose, determined the choice of the dissertation topic, its content, goals and problems. The practical significance of Makala is in the development of management algorithms and evaluation methods for innovative projects. The algorithm includes intra-stage project evaluation and methodological justification of the manager's decision-making in the implementation of the project at each stage and ensuring the need to adjust the strategy. In addition, the analysis of the main barriers to practical implementation was carried out and recommenda-tions were developed to eliminate them. The developed method includes all the prerequisites for successful application in the specific activity of the region.